FIEP – 80 YEARS COMMITTED TO PHYSICAL EDUCATION (Fiep Bulletin - online, 2014)
After many attempts to create an international organism for Physical Education, FIEP was founded in 1923. When it was created, it had close commitments with Ling Swedish Gymnastics.After the administration of Lefebure (Belgium), Einar Nerman (Sweden) and Joseph Thulin (Sweden), FIEP breaks its original ties to Swedish Gymnastics Guidelines and starts taking universal positions under the presidency of Antonio Leal de Oliveira (Portugal).The World Physical Education Manifesto was published in 1970, when Pierre Seurin (France) was FIEP?s president. Later, John Andrews (England) consolidated FIEP?s movement worldwide.Currently FIEP?s President is Manoel Tubino and FIEP once again adopts a World Physical Education Manifesto. It has been making its international goals even wider and has also reinforced its initial statutes.